HPV 16 E6/E7 Promote the Glucose Uptake of GLUT1 in Lung Cancer Through Downregulation of TXNIP Due to Inhibition of PTEN Phosphorylation - Tang, Jia-Yi; Li, Dong-Yu; He, Ling; Qiu, Xue-Shan; Wang, En-Hua; Wu, Guang-Ping (Frontiers in Oncology, 2020)
High-risk human papillomavirus (HPV) infection play an important role in the development of lung cancer. Our previously study showed that E6 and E7 in HPV16 upregulated the expression of GLUT1 in lung cancer cells. However, whether they can promote the glucose uptake by GLUT1 and the underlying molecular mechanism has not been identified. It has been reported that thioredoxin interacting protein (TXNIP) regulates both the expression of GLUT1 and its glucose uptake. We speculate that high risk HPV16 infection may be closely related to TXNIP expression. Therefore, we associate HPV16 with TXNIP to explore the potential molecular mechanism of their regulation of GLUT1 expression and glucose uptake. Using double directional genetic manipulation in lung cancer cells, we showed that HPV16 E6/E7 proteins downregulated the expression of p-PTEN in lung cancer cells, the knockdown of PTEN further inhibited the expression of TXNIP, the inhibition of TXNIP further promoted the accumulation of HIF-1α by inhibiting the translocation of nuclear HIF-1α to the cytoplasm, and subsequently upregulated the expression of GLUT1 at the protein and mRNA levels. More interestingly, we found that the knockdown of TXNIP played a decisive role to promote the glucose uptake by GLUT1. Together, these findings suggested that the PTEN-TXNIP-HIF-1α axis might be related to the E6/E7-mediated expression of GLUT1 and its glucose uptake.